Decreased Gray Matter Volume of Cuneus and Lingual Gyrus in Schizophrenia Patients with Tardive Dyskinesia is Associated with Abnormal Involuntary Movement - Ting Yu (Nature Portfolio, 2018)
Abstract Tardive dyskinesia (TD) is a devastating motor disorder associated with the etiological process of schizophrenia or antipsychotic medication treatments. To examine whether cerebral morphological changes may manifest in TD, we used voxel-based morphometry to analyze high-resolution T1-weighted brain structural magnetic resonance images from 32 schizophrenics with TD (TD group), 31 schizophrenics without TD (non-TD group), and 32 healthy controls (HC group). We also assessed psychopathological symptoms with the Positive and Negative Syndrome Scale (PANSS), and TD severity with the Abnormal Involuntary Movement Scale (AIMS). We compared gray matter volumes (GMVs) among groups, and tested for correlations between GMV changes and psychopathological symptoms or TD severity. The results showed significant differences in GMV in the frontal and temporal cortices, insula and cerebellum among the three groups. Brainstem and inferior frontal and precentral gyri GMVs were significantly larger, whereas cuneus and lingual gyrus GMVs were significantly smaller in the TD group as compared to non-TD group. Further, the cuneus and lingual gyrus GMVs were positively correlated with AIMS scores in the TD group. The current results suggest that TD may be associated with the alterations in GMV that are different from that of schizophrenics without TD. Further studies are needed to confirm and to examine the functional significance of these structural findings.